SENSIBILITIES OF THE STAKEHOLDERS IN RTE - KUKRETI, ACHLA (THE PRIMARY TEACHER, 2013)
The right to education envisages the responsibility of many in ensuring that all children of the ages 6-14 years of age receive education in schools. For this goal to be realised, the onus lies on a number of individuals and groups in the schooling chain as it exists today. The RTE for the fi rst time has dwelt upon governance of the school system at the level of each school and defi ned to some extent the role and the scope of all stakeholders in the school. This requires each individual school to evolve and develop within the wider framework of the directives from appropriate government agencies. With this kind of evolving of each school and the stakeholders’ autonomy, their resultant responsibility and accountability also become greater.